Firm heterogeneity and trade in EU countries: A cross-country analysis - Claire Giordano; Paloma López-García (European Central Bank (ECB), 2019)
Firms are heterogeneous, even within narrowly defined sectors. This paper surveys the relevant theoretical and empirical literature on firm heterogeneity and external trade. By innovatively exploiting rich cross-country micro-aggregated data sourced from the ECB Competitiveness Research Network (CompNet), this study then investigates the main implications of firm heterogeneity for trade of EU countries, showing a set of stylised facts. On the one hand, exporting firms are larger, more productive and pay higher wages than non-exporting firms. Only these firms are able to bear export costs, related to various factors, such as tariff and non-tariff trade barriers, the quality of the legal system or access to finance. Hence, only few enterprises actually export, and the intensity of aggregate export concentration within few large firms varies across countries and sectors. On the other hand, opening to trade boosts individual firms' productivity growth, via a number of channels, and also enhances allocative efficiency across firms, in turn increasing aggregate productivity growth. One of the main standard determinants of export growth, namely changes in the real effective exchange rate, impacts aggregate performance differently across countries and sectors, depending on sectoral composition and on firm characteristics within a given sector
Keywords: F14; L25; 330; Trade; firm heterogeneity; productivity; real effective exchange rates